The Association between DNA Methylation Status and Epstein-Barr Virus Infection in Laryngeal Carcinomas - Hotoboc Irina Elisaveta; Fudulu Alina; Huica Irina; Iancu Iulia Virginia; Grigore Raluca; Bertesteanu Șerban Vifor Gabriel; Bleotu Coralia; Anton Gabriela; Botezatu Anca (Romanian Journal of Internal Medicine)
Infection with Epstein-Barr virus is a known risk factor for laryngeal carcinogenesis; it might influence DNA methylation acting as an epigenetic driver in this type of malignancy.